Features of Psychological Adaptation of Training Future Teachers of Physical Culture; 8th World Conference on Educational Sciences (WCES-2016), 04-06 February 2016, Madrid, Spain - Soboleva A. A. Antonina Aleksandrovna; Khasanova R. R. Rezeda Rakhmatullovna; Andreev V. I. Vladimir Igorevich; Sarycheva T. V. Tatiana Valerievna; Smagly L. V. Lyudmila Vyacheslavovna (2016, 2016)
Title screen